2014
DOI: 10.1016/j.ejvs.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Impact, and Predictors of Cranial Nerve Palsy and Haematoma Following Carotid Endarterectomy in the International Carotid Stenting Study

Abstract: ObjectiveCranial nerve palsy (CNP) and neck haematoma are complications of carotid endarterectomy (CEA). The effects of patient factors and surgical technique were analysed on the risk, and impact on disability, of CNP or haematoma in the surgical arm of the International Carotid Stenting Study (ICSS), a randomized controlled clinical trial of stenting versus CEA in patients with symptomatic carotid stenosis.Materials and methodsA per-protocol analysis of early outcome in patients receiving CEA in ICSS is repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 18 publications
2
31
1
2
Order By: Relevance
“…In previous reports from clinical trials, the incidence of CNI was 5.1 – 8.6% 1013, 23 , consistent with these findings. Post-operative evaluation using laryngoscopy or by otolaryngologists were not systematically performed in this or any of the reference trials so the diagnosis of CNIs was made on examination by neurologists or by the surgeons who performed the operations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In previous reports from clinical trials, the incidence of CNI was 5.1 – 8.6% 1013, 23 , consistent with these findings. Post-operative evaluation using laryngoscopy or by otolaryngologists were not systematically performed in this or any of the reference trials so the diagnosis of CNIs was made on examination by neurologists or by the surgeons who performed the operations.…”
Section: Discussionsupporting
confidence: 88%
“…Few reports have included data regarding the timing of resolution of the deficits. For example, in the report from the International Carotid Stenting Study (ICSS) 13,23 , the incidence of CNI was 5.5% and little detail was provided regarding resolution of the deficits but two patients required percutaneous feeding tubes, at least temporarily. In CREST, we found that 34% of the injuries were resolved at the 1-month follow-up visit and 80.8% had resolved by the 12-month follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…23 Other single centre studies have also reported that performing CEA in patients on dual antiplatelet therapy is not associated with an increase in reexploration for neck haematomas, 24 while the International Carotid Stenting Study reported a prevalence of 3.4% for neck haematomas requiring re-exploration following 821 CEAs. 25 It is, however, conceded that the spontaneous shin haematoma was probably a direct consequence of dual antiplatelet therapy, but this was the only example of spontaneous peripheral bleeding in this series and there were no cases of acute gastrointestinal haemorrhage.…”
Section: Discussionmentioning
confidence: 88%
“…Austin Health, Heidelberg [46]: M Brooks, B Chambers (PI), A Chan, P Chu, D Clark, H Dewey, G Donnan, G Fell, M Hoare, M Molan, A Roberts and N Roberts.…”
Section: Data Sharing Statementmentioning
confidence: 99%
“…46 We analysed the effects of patient factors and surgical technique on the risk, and impact on disability, of cranial nerve palsy or haematoma in the surgical arm, including only patients allocated to endarterectomy in whom the procedure was actually initiated (per-protocol analysis). Patients who crossed over to CEA, received CEA after an attempt at CAS or received medical therapy instead of CAS were excluded.…”
Section: Incidence Impact and Predictors Of Cranial Nerve Palsy And mentioning
confidence: 99%